Air pollution prediction based on changes in monsoon wind direction by using trajectory-geospatial approach - Khairul Nizam Abdul Maulud,; Nor Diana Abdul Halim,; Wan Shafrina Wan Mohd Jaafar,; Ching, Kelvin Hwa Lun; Fazly Amri Mohd,; Firoz Khan,
Industrial areas are typically associated with hazardous levels of air pollution to human health and the environment. The growing number of factories in the area poses an ever-greater threat to the surrounding communities. One of the several incidents pointing to poor air quality in the industrial region is the severe air pollution incident that occurred in Pasir Gudang in June 2019 which brought adverse health impacts to nearby schoolchildren. This study intended to ascertain the role of meteorological factors and impacts on the dispersion of air pollution in the Pasir Gudang Industrial Area at the time of the occurrence. The air pollution distribution patterns were predicted using a trajectory-geospatial method, the Hybrid Single-Particle Lagrangian Integrated Trajectory (HYSPLIT) model and Geographic Information System to account for the impact of the monsoon by determining which areas might be hit the worst as the shifted of monsoon seasons. Based on the results, the forward-air mass trajectories showed direct influence by the wind changes in monsoon seasons (Southwest Monsoon, Northeast Monsoon, and Inter-Monsoon). The geospatial maps showed the potential areas affected by the air pollution incident were highly distributed within 1 km, associated with lower dispersion of air pollution at 1000 m above ground level height. The findings can serve as a guideline for local authorities in decision-making to develop better standard operating procedure in managing future air pollution threats and to improve industrial location planning in reducing air pollution impacts on the surrounding area.